Biochemical and cytological analyses of pleural effusion in patients with lung anthracosis and antracofibrosis. (September 2021) - Shafahi, Ahmad; Fekri, Mitra Samareh; Hashemi Bajgani, Seyed Mahdi; Yazdani, Rostam; Shafiepour, Mohsen; Touhidi, Mohammad Hassan; Sharifi, Hamid; Tayari, Fatemeh; Sharifpour, Ali
Abstract: Background: Anthracosis and anthracofibrosis are attributed to the deposition of carbon particles along with fibrosis, adhesion, narrowing, and collapse. There has been no study on the characteristics of the pleural fluid in anthracosis. The present study analyzed the biochemical characteristics of pleural effusion in patients with pulmonary anthracosis. Patients and methods: The study is a cross-sectional study which included patients who were referred to the Afzalipour Hospital in Kerman, eastern Iran. Between April 2018 and October 2019, patients who had undergone bronchoscopy and were diagnosed with anthracosis and pleural effusion were selected through the census method. The characteristics of the pleural fluid were analyzed for protein, albumin, LDH, PH, Triglyceride, cholesterol, glucose, and cytology. Concomitant blood samples were examined for LDH, albumin, total protein, and glucose. After it was specified whether the pleural effusion was transudative or exudative, patients with lymphocyte-dominant exudative pleural fluid became candidates for thoracoscopy. Result: 106 patients (6.21 %) of 1705 patients had anthracosis and anthracofibrosis; 37 of these patients (34.9 %) had coexisting pleural effusion. 31 patients gave written informed consent for thoracentesis. The mean age of the patients was 76.48 ± 8.81. In addition, 67.74 % of the patients were female. Pleural effusion was transudative in 29 (93.54 %). Except for one case, all patients had diffuse anthracofibrosis and 67.74 % of the patients had a history of baking bread. Conclusion: According to the findings of this study, most cases had transudative lymphocyte-dominant pleural fluid with mostly diffuse anthracofibrosis. In addition, this condition is more prevalent in women, with a prevalence of approximately twice that of men. Highlights: Biochemical and cytological analyses of pleural effusion in patients with lung anthracosis and antracofibrosis. The observation of the transudative fluid with lymphocytosis in pleural effusion of patients with anthracosis. In this study, the incidence of anthracnose or anthracofibrosis with pleural effusion was more common in women.